1995
DOI: 10.1002/art.1790080407
|View full text |Cite
|
Sign up to set email alerts
|

The impact of arthritis in rural populations

Abstract: Objective. Rural residents may experience more arthritis and disability than urban dwellers. This paper reviews data on arthritis in rural areas and describes a new study, the Johnston County Osteoarthritis Project, a population‐based study of osteoarthritis (OA) of the knee and hip in rural North Carolina. Methods. Published reports of urban and rural comparisons of arthritis were reviewed. Data from the first 1,432 African‐American and Caucasian participants in the Johnston County Osteoarthritis Project were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
140
1
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(155 citation statements)
references
References 16 publications
8
140
1
6
Order By: Relevance
“…Jordan et al found that at the time of presentation, 28 % of patients with hip pain already had advanced stages of osteoarthritis on radiographic analysis [27]. Additionally, the use of opioid medications as a first-line treatment is becoming more prevalent among patients with osteoarthritis even though their use for an extended period of time prior to surgery may more likely cause opioid-induced hyperalgesia and a prolonged recovery [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Jordan et al found that at the time of presentation, 28 % of patients with hip pain already had advanced stages of osteoarthritis on radiographic analysis [27]. Additionally, the use of opioid medications as a first-line treatment is becoming more prevalent among patients with osteoarthritis even though their use for an extended period of time prior to surgery may more likely cause opioid-induced hyperalgesia and a prolonged recovery [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the TKR Patient Outcomes Research Team (PORT) multisite, prospective study reported 12-month post-TKR function actually declined in 19% of participants while other patients reported functional gains more than three times the average [12]. Previous TKR outcomes research and recent reviews have identified consistent predictors of post-TKR function yet concluded no one patient attribute or surgical factor offered a satisfactory explanation for this outcome variation [11,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous large-scale studies have found the prevalence of radiographic hip OA in US men and women older than 55 years to vary by nearly a factor of 10, between a low prevalence of 2.7%, reported in the first National Health and Nutrition Examination Survey, up to a high prevalence of 25.1%, reported in the Johnston County Osteoarthritis Project (7,8). Despite the variance in prevalence in these studies, European studies have shown that the prevalence of radiographic hip OA has remained constant throughout the past 4 decades within an urban population (9).…”
Section: Introductionmentioning
confidence: 99%
“…Results of a small study of nearly 200 people from South Africa reported a hip OA prevalence rate of only 2% in their black population (24). A large-scale study of a rural population in North Carolina showed the prevalence of hip OA to be nearly equal between blacks and whites, with overall prevalences of 29.9% and 26.4%, respectively (8). We acknowledge that it is difficult to interpret the data for the racial servicemember category of other because it is made up of numerous ethnicities; however, after adjusting for the covariant risk factors, the other racial servicemember cate- * E1-E4 ϭ junior enlisted ranks; O1-O3 ϭ junior officer ranks; E5-E9 ϭ senior enlisted ranks; O4 -O9 ϭ senior officer ranks.…”
mentioning
confidence: 99%